A mouse model of cone photoreceptor function loss (cpfl9) with degeneration due to a mutation in Gucy2e - Naggert, Anna S. E. N.; Collin, Gayle B.; Wang, Jieping; Krebs, Mark P.; Chang, Bo (Frontiers in Molecular Neuroscience, 2023)
During routine screening of mouse strains and stocks by the Eye Mutant Resource at The Jackson Laboratory for genetic mouse models of human ocular disorders, we identified cpfl9, a mouse model with cone photoreceptor function loss. The mice exhibited an early-onset phenotype that was easily recognized by the absence of a cone-mediated b-wave electroretinography response and by a reduction in rod-mediated photoresponses at four weeks of age. By genetic mapping and high-throughput sequencing of a whole exome capture library of cpfl9, a homozygous 25 bp deletion within exon 11 of the Gucy2e gene was identified, which is predicted to result in a frame shift leading to premature termination. The corresponding protein in human, retinal guanylate cyclase 1 (GUCY2D), plays an important role in rod and cone photoreceptor cell function. Loss-of-function mutations in human GUCY2D cause LCA1, one of the most common forms of Leber congenital amaurosis, which results in blindness at birth or in early childhood. The early loss of cone and reduced rod photoreceptor cell function in the cpfl9 mutant is accompanied by a later, progressive loss of cone and rod photoreceptor cells, which may be relevant to understanding disease pathology in a subset of LCA1 patients and in individuals with cone-rod dystrophy caused by recessive GUCY2D variants. cpfl9 mice will be useful for studying the role of Gucy2e in the retina.